Applications of Ultrasonic Brain Imaging and Transcranial Ultrasound Therapy in Brain Injury Rehabilitation - WU Yi (康复学报)
Ultrasound was widely used in clinical practice as a tool for diagnosis and treatment. With the development of technology, the research and development of new algorithms and high-sensitivity ultrasound transducers have made up for the attenuation of ultrasound in the skull to a certain extent, and realized the application of ultrasound in the field of brain science. The advantages of ultrasound technology are non-invasive, safe, portable, low-cost and radiation-free, which has a great potential in the detection and rehabilitation of brain injury. Ultrasonic brain imaging techniques such as transcranial doppler (TCD), functional ultrasound imaging (fUS) and ultrasound localization microscopy (ULM) improve the signal to noise ratio by signal superposition or the cavitation effect of microbubbles, and achieve a higher resolution than CT and MRI in cerebral angiography. These ultrasound brain imaging techniques can obtain real-time images of brain tissue structures and quantify cerebral hemodynamic parameters. It can also be combined with EEG to simultaneously record the changes of the cerebral blood flow and neural activities, so as to conduct multi-dimensional evaluation of the neurovascular function after the occurrence of cerebrovascular disease. In terms of ultrasound treatment, transcranial focused ultrasound can penetrate the skull noninvasively and focus accurately on the cortex or deep brain tissues. High intensity focused ultrasound (HIFU) and low intensity focused ultrasound (LIFU) use the thermal and mechanical effects respectively to perform tissue ablation, blood-brain barrier opening, drug targeted delivery, ultrasound-assisted catheter-directed thrombolysis and neuromodulation, and can be applied to the treatment of brain tumors, brain trauma, stroke, Parkinson's disease, Alzheimer's disease, epilepsy, depression and other neurological diseases and mental diseases. At present, ultrasound brain imaging and therapeutic transcranial ultrasound are still in development. In the future, it is necessary to make further efforts to solve the problems such as cranial attenuation effect, 3D imaging development, establishment of the standard parameters on ultrasound neuromodulation and the reduction of the side effects in hearing. Meanwhile, more clinical researches will be conducted to provide strong support for the applications of ultrasound brain imaging and non-invasive transcranial ultrasound treatment in the diagnosis and rehabilitation of brain injury diseases.